2016
DOI: 10.1007/s00018-016-2376-x
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of mRNA decay in plant responses to salt and osmotic stress

Abstract: Plant acclimation to environmental stresses requires fast signaling to initiate changes in developmental and metabolic responses. Regulation of gene expression by transcription factors and protein kinases acting upstream are important elements of responses to salt and drought. Gene expression can be also controlled at the post-transcriptional level. Recent analyses on mutants in mRNA metabolism factors suggest their contribution to stress signaling. Here we highlight the components of mRNA decay pathways that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(24 citation statements)
references
References 112 publications
(205 reference statements)
2
22
0
Order By: Relevance
“…Transcripts for which abundance is affected by salt stress and that modulate main root (MR) elongation remain unknown. Drawings of proteins and processes were reproduced from the model published in Kawa and Testerink (2017). Dashed lines indicate proposed processes that have not been experimentally validated.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Transcripts for which abundance is affected by salt stress and that modulate main root (MR) elongation remain unknown. Drawings of proteins and processes were reproduced from the model published in Kawa and Testerink (2017). Dashed lines indicate proposed processes that have not been experimentally validated.…”
Section: Discussionmentioning
confidence: 99%
“…Identification of VCS as a direct substrate of SnRK2 subclass 1 protein kinases, and the emerging role of mRNA metabolism factors in osmotic and salt stress responses, suggests that VCS, similarly to subclass 1 SnRK2s, might be involved in stress-regulated modulations of root system architecture (Kawa and Testerink, 2017;Soma et al, 2017). Therefore, we tested two artifical micro RNA (amiRNA) lines targeting VCS (VCS2 and VCS4; Soma et al, 2017) and two loss-of-function mutants in XRN4 (xrn4-5 and xrn4-6; Souret et al, 2004;Gy et al, 2007) in the same experimental set up as for snrk2.1/2.4/2.5/2.9/2.10.…”
Section: Snrk24 and Snrk210 Physically Interact With Proteins Involmentioning
confidence: 99%
“…Under stress conditions, FC1 synthesizes haem in plastids, which generates a retrograde signal suppressing CCEs gene expression in the nucleus and slows down leaf senescence contributing to plant defense [Colour figure can be viewed at wileyonlinelibrary.com] pFC1FC2(fc1/fc1) line, the FC1-promoter-driven FC2 transcript accumulation was transiently increased only at the beginning of the stress treatment but remained low upon extended stress exposure ( Figure S6). Thus, the mRNA abundance under stress could generally be affected by transcriptional and posttranscriptional control (Kawa & Testerink, 2017), and we did not exclude a faster turnover of FC2 mRNA under abiotic stress. Keeping this in mind, we wish to emphasize that the dramatic stress-dependent reduction of FC2 content cannot substitute for the deficiency of stress inducible FC1 expression.…”
Section: In Arabidopsis Fc2 Can Fully Substitute Fc1 Function Undementioning
confidence: 99%
“…In particular, regulation of mRNA abundance by the epigenome (Jiang et al 2014;Wong et al 2017) and by transcription factors (Song et al 2016) has been a primary focus in elucidation of mechanisms responsible for dynamic environmental regulation of the transcriptome. Post-transcriptional regulation, including alternative polyadenylation, splicing, localization, and degradation has received less attention, but also can substantially impact mRNA abundance (Floris et al 2009;Walley and Dehesh 2010;Feng et al 2015;Kawa and Testerink 2017;Wong et al 2017;Gu et al 2018;Sorenson et al 2018). Changes in mRNA secondary and tertiary structures influence post-transcriptional processes (Bevilacqua et al 2016), as revealed by many examples based on in depth analysis of specific transcripts (Zaug and Cech 1995;Hull et al 2016).…”
Section: Introductionmentioning
confidence: 99%